Primer for capacitor device electrodes, composition for forming a primer layer, electrode for capacitor device and secondary battery

A fluorine-containing copolymer primer layer with adhesive functional groups addresses the adhesion issue in secondary batteries, improving charge-discharge cycle and discharge rate characteristics by enhancing the bond between the current collector and electrode active material layer.

KR103044407B1Active Publication Date: 2026-11-05AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020237030218
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-24
Filing Date
2022-03-23
Publication Date
2026-11-05
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

Secondary batteries using fluorine-containing or hydrocarbon-based polymer binders exhibit insufficient adhesion to current collectors, leading to poor charge-discharge cycle characteristics and discharge rate characteristics.

Method used

A primer layer is formed between the current collector and the electrode active material layer using a fluorine-containing copolymer with adhesive functional groups, such as carbonyl-containing groups and hydroxyl groups, and a melting point of 150°C or higher, along with a conductive material, to enhance adhesion.

Benefits of technology

The primer layer improves the adhesion between the current collector and electrode active material layer, resulting in enhanced charge-discharge cycle characteristics and discharge rate characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112023097868603-PCT00001
    Figure 112023097868603-PCT00001
  • Figure 112023097868603-PCT00002
    Figure 112023097868603-PCT00002
Patent Text Reader

Abstract

A secondary battery having excellent charge / discharge cycle characteristics (capacity retention rate) or discharge rate characteristics (discharge capacity ratio), and a primer for an electrode of a storage device for obtaining the secondary battery, a composition for forming a primer layer, and an electrode for a storage device are provided. A primer for a capacitor device electrode for forming a primer layer formed between a current collector and an electrode active material layer, comprising a fluorine-containing copolymer having a unit based on tetrafluoroethylene or chlorotrifluoroethylene, and a unit based on ethylene, hexafluoropropylene or perfluoro(alkyl vinyl ether), substantially not having a unit based on vinylidene fluoride, and also having an adhesive functional group capable of reacting with hydroxyl groups or forming hydrogen bonds.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a primer for an electrode of a capacitor device, a composition for forming a primer layer, an electrode for a capacitor device, and a secondary battery. Background Technology

[0002] Energy storage devices, such as secondary batteries, are typically composed of electrodes, a non-aqueous electrolyte, a separator, and the like as major components. Electrodes for energy storage devices are generally manufactured by applying an electrode composite containing an electrode active material, a conductive material, a binder, and a liquid medium onto the surface of a current collector and drying it.

[0003] It is known that fluorine-containing polymers or hydrocarbon-based polymers are used as binders for electrode composites for capacitor devices.

[0004] However, electrode composites containing fluorine-containing polymers or hydrocarbon-based polymers are prone to having insufficient adhesion to the surface of the current collector.

[0005] For this reason, secondary batteries using electrodes manufactured using binders containing fluorine-containing polymers or hydrocarbon-based polymers do not obtain sufficient charge-discharge cycle characteristics (capacity retention rate) or discharge rate characteristics (discharge capacity ratio).

[0006] Therefore, in Patent Document 1, it is proposed to improve the adhesion of the electrode composite for a capacitor device to the surface of the current collector by forming a base layer on the current collector in advance and then applying the electrode composite for a capacitor device.

[0007] In Patent Document 1, a polyurethane resin or an epoxy resin is disclosed as a primer layer. Prior art literature

[0008] Japanese Published Patent Application No. Hei 10-149810 The problem to be solved

[0009] However, as in Patent Document 1, if a polyurethane resin or an epoxy resin is used as the undercoat layer, the undercoat layer deteriorates during the charging and discharging of the secondary battery, making it impossible to maintain the adhesion of the electrode composite for the capacitor device to the surface of the current collector, and consequently, sufficient charge-discharge cycle characteristics (capacity retention rate) or discharge rate characteristics (discharge capacity ratio) cannot be obtained.

[0010] The present invention is made in consideration of the above circumstances and aims to provide a secondary battery having excellent charge-discharge cycle characteristics (capacity retention rate) or discharge rate characteristics (discharge capacity ratio), a primer for an electrode of a storage device for obtaining the secondary battery, a composition for forming a primer layer, and an electrode for a storage device. means of solving the problem

[0011] To achieve the above objective, the present invention adopts the following configuration.

[0012] [1] A primer for a capacitor device electrode to form a primer layer formed between the current collector and the electrode active material layer,

[0013] A primer for an electrode of a capacitor device comprising a fluorine-containing copolymer having a unit based on tetrafluoroethylene or chlorotrifluoroethylene, and a unit based on ethylene, hexafluoropropylene or perfluoro(alkyl vinyl ether), substantially not having a unit based on vinylidene fluoride, and also having an adhesive functional group capable of reacting with or forming a hydrogen bond with a hydroxyl group.

[0014] [2] A primer described in [1] having a melting point of 150°C or higher of the above-mentioned fluorine copolymer.

[0015] [3] The primer described in [1] or [2], wherein the above fluorine copolymer has one or more types selected from the group consisting of carbonyl-containing groups and hydroxyl groups as adhesive functional groups.

[0016] [4] The primer described in [3], wherein the above fluorine copolymer has at least one carbonyl containing group selected from the group consisting of a carbonyl group between carbon atoms of a hydrocarbon group, a carbonate group, a carboxyl group, a haloformyl group, an alkoxycarbonyl group, and an acid anhydride group as the adhesive functional group.

[0017] [5] A primer described in any one of [1] to [4], wherein the above-mentioned fluorine copolymer comprises a unit based on tetrafluoroethylene.

[0018] [6] A primer described in any one of [1] to [5], wherein the above-mentioned fluorine copolymer comprises ethylene-based units.

[0019] [7] A primer described in any one of [1] to [6], wherein the above-mentioned fluorine copolymer comprises a tetrafluoroethylene-based unit and an ethylene-based unit.

[0020] [8] Additionally, a primer described in any one of [1] to [7] containing a conductive material.

[0021] [9] A composition for forming a primer layer comprising a primer for a capacitor device electrode and a liquid medium as described in any one of [1] to [8] above.

[0022]

[10] The above liquid medium is one or more selected from the group consisting of aqueous media, aliphatic, aromatic hydrocarbons, alcohols, ethers, esters, ketones, nitrogen-containing compounds, sulfur-containing compounds, and fluorine-containing compounds, as described in [9].

[0023]

[11] The above liquid medium is one or more selected from the group consisting of an aqueous medium, N-methylpyrrolidone, N,N-dimethylacetamide, and an aliphatic hydrocarbon compound having 6 to 10 carbon atoms having one carbonyl group, [9] the composition described therein.

[0024]

[12] An electrode for a capacitor having a current collector and an electrode active material layer formed on the current collector, wherein between the current collector and the electrode active material layer, a primer layer comprising a primer for a capacitor electrode described in any one of [1] to [8].

[0025]

[13] An electrode for a capacitor having a current collector and an electrode active material layer formed on the current collector, wherein between the current collector and the electrode active material layer, a primer layer formed by a primer layer forming composition described in any one of [9] to

[11] .

[0026]

[14] An electrode for a capacitor having a current collector and an electrode active material layer formed on the current collector, wherein between the current collector and the electrode active material layer, a primer layer formed of a primer for a capacitor electrode described in any one of [1] to [8] is formed.

[0027]

[15] A secondary battery having an electrode and an electrolyte for a capacitor device as described in any of

[12] to

[14] above. Effects of the invention

[0028] According to the primer for a capacitor device electrode, the composition for forming a primer layer, the electrode for a capacitor device, and the secondary battery of the present invention, excellent charge-discharge cycle characteristics (capacity retention rate) or discharge rate characteristics (discharge capacity ratio) are obtained. Specific details for implementing the invention

[0029] The definitions of the following terms in this specification and claims are as follows.

[0030] "Monomer-based units" is a general term for atomic groups formed directly by the polymerization of one molecule of monomer and atomic groups obtained by chemically transforming a part of the said atomic groups. In this specification, monomer-based units are also simply referred to as monomer units.

[0031] "Monomer" refers to a compound having a polymerizable carbon-carbon double bond.

[0032] "Melting point" refers to the temperature corresponding to the maximum value of the melting peak measured by differential scanning calorimetry (DSC).

[0033] "Carbonyl group" refers to a group having a carbonyl group (-C(=O)-) in its structure.

[0034] "Acid anhydride" refers to a group represented as -C(=O)-OC(=O)-.

[0035] The “average particle size” of the polymer is a value calculated by cumulant method analysis from the autocorrelation function obtained by dynamic light scattering for a sample in which the polymer is diluted with water to a solid content concentration of 1 mass%.

[0036] [MFR (Melt Flow Rate)] is a value (g / 10 min) calculated by measuring the mass (g) of copolymer flowing out in 10 minutes from an orifice with a diameter of 2 mm and a length of 8 mm under conditions of a temperature of 220 °C, 297 °C, or 380 °C and a load of 49 N, using a melt indexer (manufactured by Deckno Seven Co., Ltd.) in accordance with ASTM D3159. Additionally, regarding the temperature at which measurement is taken, a temperature 30 to 80 °C higher than the melting point is selected based on the relationship with the melting point. For example, if the melting point is 300 °C, the measurement is taken at 380 °C; if the melting point is 255 °C, the measurement is taken at 297 °C; and if the melting point is 183 °C, the measurement is taken at 220 °C.

[0037] The "main chain" of a polymer refers to a polymer chain formed by the connection of two or more monomers.

[0038] In this specification, a compound represented by Formula 1 may also be described as “Compound 1”.

[0039] <Primer for Capacitive Device Electrodes>

[0040] The primer for the electrode of the capacitor device according to the present invention (hereinafter also simply referred to as "primer") contains a specific fluorine-containing copolymer (hereinafter also referred to as "copolymer A"). In addition, the primer of the present invention may include, if necessary, a polymer other than copolymer A, additives, etc., in addition to copolymer A, to the extent that it does not impede the effects of the present invention.

[0041] [Copolymer A]

[0042] Copolymer A has a unit based on tetrafluoroethylene (hereinafter also referred to as “TFE”) or chlorotrifluoroethylene (hereinafter also referred to as “CTFE”) (hereinafter also referred to as “unit a”), and a unit based on ethylene (hereinafter also referred to as “E”), hexafluoropropylene (hereinafter also referred to as “HFP”) or perfluoro(alkyl vinyl ether) (hereinafter also referred to as “PAVE”) (hereinafter also referred to as “unit b”), substantially does not have a unit based on vinylidene fluoride (hereinafter also referred to as “VdF”) (hereinafter also referred to as “VdF unit”), and also has an adhesive functional group capable of reacting with hydroxyl groups or forming hydrogen bonds.

[0043] "Substantially not having VdF units" means not having VdF units, or having VdF units to an extent that does not affect the chemical resistance of the copolymer, and "not affecting the chemical resistance of the copolymer" means, for example, that the VdF units are 1 mol% or less relative to the units based on the total monomers of copolymer A. When VdF-based units are present, it is preferable that the VdF units are 0.5 mol% or less relative to the units based on the total monomers of copolymer A.

[0044] Copolymer A may have units based on monomers other than the above (excluding VdF) to the extent that it does not impede the effects of the present invention.

[0045] Copolymer A has a unit based on TFE (hereinafter also referred to as "TFE unit") or a unit based on CTFE (hereinafter also referred to as "CTFE unit") as unit a, and may have both the TFE unit and the CTFE unit.

[0046] In terms of good chemical resistance or oxidation resistance, copolymer A preferably has at least a TFE unit as unit a, and more preferably has only a TFE unit.

[0047] Copolymer A has, as unit b, an ethylene-based unit (hereinafter also referred to as "E unit"), an HFP-based unit (hereinafter also referred to as "HFP unit"), or a PAVE-based unit (hereinafter also referred to as "PAVE unit"), and may have two or three types of these units.

[0048] In terms of improving adhesion between the current collector and the electrode active material layer, copolymer A preferably has at least E units as unit b, and more preferably has only E units.

[0049] PAVE is preferably Compound 1 represented by Formula 1 below. Two or more types of Compound 1 may be used.

[0050] CF2=CFOR f1 ···Equation 1

[0051] [In Equation 1, R f1 [It is a group containing oxygen atoms between carbon atoms of a perfluoroalkyl group having 1 to 10 carbon atoms, or a perfluoroalkyl group having 2 to 10 carbon atoms.]

[0052] In Equation 1, R f1In terms of the excellent chemical resistance of copolymer A, a perfluoroalkyl group having 1 to 6 carbon atoms is preferred, and a perfluoroalkyl group having 1 to 3 carbon atoms is more preferred.

[0053] As monomers other than those mentioned above, in addition to the monomer having an adhesive functional group described later, CH2=CY(CF2) n Examples include fluorine-containing vinyl monomers other than the above, such as compounds represented by Z (where Y and Z are each independently a fluorine atom or a hydrogen atom, and n is 2 to 10), olefin-based vinyl monomers other than ethylene such as propylene, vinyl ethers other than PAVE, vinyl esters, and halogen-containing vinyl monomers having halogen atoms other than fluorine atoms. Two or more types of monomers other than the above may be used.

[0054] In the above FAE, n in the formula is 2 to 10, 2 to 8 is preferred, 2 to 6 is more preferred, and 2, 4, and 6 are particularly preferred. If n is 2 or greater, it becomes difficult for cracks to form in the primer layer, and it becomes easier to maintain the adhesion between the current collector and the electrode active material layer. If n is 10 or less, chemical resistance is excellent. Two or more types of FAE may be used.

[0055] Preferred specific examples of such FAE include CH2=CH(CF2)2F, CH2=CH(CF2)4F, CH2=CH(CF2)6F, CH2=CF(CF2)3H, etc. As for FAE, CH2=CH-R f2 (R f2 A perfluoroalkyl group having 2 to 6 carbon atoms (hereinafter the same) is most preferable.

[0056] It is preferable that copolymer A has a TFE unit as unit a and an E unit as unit b.

[0057] Copolymer A having TFE and E units includes E / TFE copolymer, E / TFE / HFP copolymer, and E / TFE / CH2=CH-R f2 Copolymer, E / TFE / CF2=CFOR f1 and E / TFE / HFP / CH2=CH-R f2 Copolymers are preferred. Among them, E / TFE copolymers, E / TFE / CH2=CH-R f2 Copolymers, E / TFE / HFP copolymers are preferred, and E / TFE copolymers and E / TFE / CH2=CH-R f2 Copolymers are particularly desirable.

[0058] In addition, an E / TFE copolymer refers to a copolymer having E units and TFE units. The same applies to other copolymers.

[0059] The preferred ratio of each unit when copolymer A has a TFE unit as unit a and an E unit as unit b is as follows.

[0060] The ratio of TFE units is preferably 25 to 80 mol% with respect to the total amount of E units and TFE units, more preferably 40 to 65 mol%, and even more preferably 45 to 63 mol%. If the ratio of TFE units is 25 mol% or more, chemical resistance is excellent. If the ratio of E units is 20 mol% or more, the adhesion between the current collector and the electrode active material layer is good.

[0061] When copolymer A has TFE units and E units, and also has units based on monomers other than monomers having adhesive functional groups, the ratio of units based on monomers other than monomers having adhesive functional groups is preferably 0.1 to 10.0 mol% with respect to the total amount of E units and TFE units, more preferably 0.2 to 8.0 mol%, even more preferably 0.3 to 6.0 mol%, and particularly preferably 0.4 to 4.0 mol%.

[0062] As for the adhesive functional group in copolymer A, a functional group selected from the group consisting of carbonyl containing groups, hydroxyl groups, epoxy groups, amide groups, amino groups, and isocyanate groups is preferred. The adhesive functional groups in copolymer A may be two or more types.

[0063] As for the adhesive functional groups in copolymer A, carbonyl-containing groups and hydroxyl groups are preferred in terms of adhesion to the current collector and the electrode active material layer. Among these, carbonyl-containing groups are preferred.

[0064] Examples of carbonyl-containing groups include groups having a carbonyl group between carbon atoms of a hydrocarbon group, carbonate groups, carboxyl groups, haloformyl groups, alkoxycarbonyl groups, acid anhydride groups, etc.

[0065] Among these, an acid anhydride group and a carboxyl group are preferred, and an acid anhydride group is particularly preferred.

[0066] Examples of hydrocarbon groups having carbonyl groups between carbon atoms of a hydrocarbon group include alkylene groups having 2 to 8 carbon atoms. The number of carbon atoms in an alkylene group is the number of carbon atoms that does not include carbon atoms of a carbonyl group. The alkylene group may be in a straight chain form or a branched form.

[0067] A haloformyl group is represented as -C(=O)-X (where X is a halogen atom). Examples of halogen atoms in a haloformyl group include fluorine atoms and chlorine atoms, and fluorine atoms are preferred.

[0068] As for the alkoxy group in the alkoxycarbonyl group, it may be a straight chain type or a branched type, and an alkoxy group having 1 to 8 carbon atoms is preferred, and a methoxy group and an ethoxy group are more preferred.

[0069] The content of adhesive functional groups in copolymer A is 1 × 10 carbon atoms in the main chain of copolymer A 6For each piece, 10 to 60,000 are preferred, 100 to 50,000 are more preferred, 100 to 10,000 are even more preferred, and 300 to 5,000 are particularly preferred. If the content of adhesive functional groups is within the above range, the adhesion to the current collector and the electrode active material layer is even better.

[0070] The content of adhesive functional groups can be measured by methods such as nuclear magnetic resonance (NMR) analysis and infrared absorption spectrum analysis. For example, as described in Japanese Patent Publication No. 2007-314720, the ratio (mol%) of units having adhesive functional groups among the total units constituting the fluorine-containing copolymer can be determined using methods such as infrared absorption spectrum analysis, and the content of adhesive functional groups can be calculated from this ratio.

[0071] It is preferable that the adhesive functional group be present in at least one of the terminal group of the main chain and the pendant group of the main chain of copolymer A in terms of adhesion to the current collector and the electrode active material layer.

[0072] Copolymer A, in which an adhesive functional group is present at least one of the terminal group of the main chain and the pendant group of the main chain, can be prepared by methods such as copolymerizing a monomer having an adhesive functional group during the polymerization of the monomer, or polymerizing the monomer using a chain transfer agent or a polymerization initiator that results in an adhesive functional group. These methods may also be used in combination.

[0073] In particular, it is preferable to produce a copolymer having the monomer unit by copolymerizing a monomer having an adhesive functional group, thereby making copolymer A in which the adhesive functional group exists as at least a pendant group of the main chain.

[0074] As for monomers having adhesive functional groups, monomers having carbonyl containing groups, hydroxyl groups, epoxy groups, amide groups, amino groups, or isocyanate groups are preferred, monomers having carbonyl containing groups are more preferred, cyclic hydrocarbon monomers having acid anhydride groups (hereinafter also referred to as "acid anhydride monomers") and monomers having carboxyl groups are more preferred, and acid anhydride monomers are particularly preferred.

[0075] Examples of acid anhydride monomers include itaconic anhydride (hereinafter also referred to as “IAH”), citraconic anhydride (hereinafter also referred to as “CAH”), 5-norbornene-2,3-dicarboxylic acid anhydride (hereinafter also referred to as “NAH”), maleic anhydride, etc.

[0076] Two or more types of acid anhydride monomers may be used in combination.

[0077] As acid anhydride monomers, IAH, CAH, and NAH are preferred. By using any of IAH, CAH, and NAH, copolymer A having an acid anhydride group can be easily produced without using a special polymerization method that is required when maleic anhydride is used (see Japanese Patent Publication No. Hei 11-193312).

[0078] As for acid anhydride monomers, IAH and NAH are particularly preferred in that they have superior adhesion to the current collector and the electrode active material layer.

[0079] In addition, when an acid anhydride monomer is used, some of the acid anhydride groups in the acid anhydride monomer are hydrolyzed, and copolymer A may contain units based on a dicarboxylic acid corresponding to the acid anhydride monomer (itaconic acid, citraconic acid, 5-norbornene-2,3-dicarboxylic acid, maleic acid, etc.).

[0080] Monomers having a carboxyl group include maleic acid, itaconic acid, citraconic acid, and undecylenic acid.

[0081] Examples of monomers having hydroxyl groups include hydroxyalkyl vinyl ethers.

[0082] Examples of monomers having an epoxy group include epoxyalkyl vinyl ether.

[0083] When copolymer A has units based on monomers having adhesive functional groups, the proportion of said units is preferably 0.01 to 5.0 mol% with respect to the total number of monomer-based units in copolymer A, more preferably 0.05 to 3.0 mol%, and even more preferably 0.1 to 2.0 mol%.

[0084] If the ratio of units based on monomers having adhesive functional groups is 0.01 mol% or more, the adhesion to the current collector and the electrode active material layer is excellent. If it is 0.05 mol% or more, the adhesion is better, and if it is 0.1 mol% or more, it is even better. If the ratio of units based on monomers having adhesive functional groups is 5.0 mol% or less, the chemical resistance or oxidation resistance is excellent. If it is 3.0 mol% or less, the chemical resistance or oxidation resistance is better, and if it is 2.0 mol% or less, it is even better.

[0085] As chain transfer agents that produce adhesive functional groups, chain transfer agents having carboxyl groups, ester bonds, hydroxyl groups, etc. are preferred. Specifically, examples include acetic acid, acetic anhydride, methyl acetate, ethylene glycol, propylene glycol, etc.

[0086] As a polymerization initiator that produces adhesive functional groups, peroxide polymerization initiators such as peroxycarbonate, diacyl peroxide, and peroxyester are preferred.

[0087] Specifically, examples include di-n-propylperoxydicarbonate, diisopropylperoxycarbonate, tert-butylperoxyisopropylcarbonate, bis(4-tert-butylcyclohexyl)peroxydicarbonate, di-2-ethylhexylperoxydicarbonate, etc.

[0088] The shape of copolymer A used as a primer is preferably particulate, as it offers excellent miscibility with other components such as conductive materials. In the case of particulates, the average particle size is preferably 0.01 to 50 μm, and more preferably 0.01 to 20 μm.

[0089] Since the average particle size is 0.01 μm or larger, it is easy to function as a binder for other components such as conductive materials. Since the average particle size is 50 μm or smaller, it has excellent compatibility with other components such as conductive materials.

[0090] Particulate copolymer A may be dispersed in a liquid medium or may be in powder form.

[0091] Copolymer A is preferably at least 150°C, more preferably at 160°C to 320°C, and even more preferably at 180°C to 260°C.

[0092] Since the melting point is 150°C or higher, the function is maintained even at high temperatures. Since the melting point is 320°C or lower, the processability is excellent.

[0093] The MFR of copolymer A is preferably 0.1 to 200, and preferably 1 to 100. Since the MFR is 0.1 or higher, moldability is excellent. Since the MFR is 200 or lower, the mechanical strength of the primer is excellent, and the adhesion to the electrode active material layer and the current collector is excellent.

[0094] Copolymer A can be prepared by conventional methods. For example, it can be prepared by polymerizing TFE with ethylene and an acid anhydride monomer.

[0095] When polymerizing monomers, it is preferable to use a radical polymerization initiator.

[0096] Polymerization methods include bulk polymerization, solution polymerization using an organic solvent (fluorohydrocarbon, chlorinated hydrocarbon, fluorinated chlorinated hydrocarbon, alcohol, hydrocarbon, etc.), suspension polymerization using an aqueous medium and, if necessary, a suitable organic solvent, and emulsion polymerization using an aqueous medium and an emulsifier, and solution polymerization is preferred.

[0097] When polymerizing TFE, ethylene, and an acid anhydride monomer, the concentration of the acid anhydride monomer during polymerization is preferably 0.01 to 5 mol% relative to the total monomer, more preferably 0.1 to 3 mol%, and even more preferably 0.1 to 2 mol%. If the concentration of the acid anhydride monomer is within the above range, the polymerization rate becomes appropriate. If the concentration of the acid anhydride monomer is excessively high, the polymerization rate tends to decrease.

[0098] As the acid anhydride monomer is consumed by polymerization, it is desirable to supply the consumed amount into the polymerization vessel continuously or intermittently to maintain the concentration of the acid anhydride monomer within the above range.

[0099] [Other polymers]

[0100] The primer of the present invention may include a polymer having a function as a primer other than copolymer A, to the extent that it does not impede the effects of the present invention.

[0101] Polymers other than copolymer A include polytetrafluoroethylene, tetrafluoroethylene-propylene copolymer, polyimide, polyamideimide, polyetherimide, polyetheretherketone, polyetherketoneketone, polyphenylenesulfide, polyethersulfone, polysulfone, polyamide, polyphenyleneether, polymethacrylate, polymethylmethacrylate, polyacrylonitrile, polycarbonate, etc.

[0102] When the primer of the present invention comprises a polymer other than copolymer A, the proportion of copolymer A in the total polymer is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more.

[0103] If the proportion of copolymer A is 50 mass% or more, it is easy to sufficiently obtain the effects of the present invention.

[0104] In addition, the primer of the present invention may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, or tetrafluoroethylene-vinylidene fluoride copolymer as a polymer other than copolymer A, but it is preferable not to include them. When the primer of the present invention includes polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, or tetrafluoroethylene-vinylidene fluoride copolymer, the total amount is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 1 mass% or less.

[0105] [Challenge]

[0106] The primer of the present invention preferably contains a conductive material. By containing a conductive material, the increase in the internal resistance of the secondary battery can be suppressed.

[0107] Examples of conductive materials include conductive carbons such as acetylene black, ketjen black, carbon black, graphite, vapor-grown carbon fibers, and carbon nanotubes.

[0108] The content of the conductive material in the primer is preferably 30 to 95 mass% with respect to the total solid content of the primer, and more preferably 45 to 85 mass%.

[0109] Conductivity is improved and the function as a battery is enhanced when the content of the conductive material is above a desirable lower limit. Adhesion to the current collector and the electrode active material layer is excellent when the content of the conductive material is below a desirable upper limit.

[0110] [Additives]

[0111] The primer of the present invention may contain various known additives. Examples of additives include emulsifiers, defoaming agents, leveling agents, preservatives, pH adjusters, dispersants such as cellulose-based resins, acrylic-based resins, urethane-based resins, and urea-based resins, radical scavengers such as hindered amine-based light stabilizers (HALS), and hydroxide agents such as magnesium oxide and calcium hydroxide.

[0112] <Composition for forming a primer layer>

[0113] It is preferable to use copolymer A, which is the primer of the present invention, and other polymers, conductive materials, and additives contained as needed, by dispersing or dissolving them in a liquid medium to form a primer layer. The composition for forming a primer layer according to the present invention is a composition comprising the primer of the present invention and a liquid medium.

[0114] Furthermore, the primer layer obtained using the primer layer forming composition of the present invention does not contain a liquid medium. In addition, the primer layer in the electrode for a capacitor device described below may be manufactured without using a liquid medium.

[0115] There are no particular limitations on the type of liquid medium, but it is preferable that the liquid medium be selected from the group consisting of aqueous media, aliphatic compounds, aromatic hydrocarbons, alcohols, ethers, esters, ketones, nitrogen-containing compounds, sulfur-containing compounds, and fluorine-containing compounds. As for the liquid medium, it is more preferable that the liquid medium be selected from the group consisting of aqueous media, N-methylpyrrolidone, N,N-dimethylacetamide, and aliphatic hydrocarbon compounds having 6 to 10 carbon atoms and one carbonyl group (hereinafter also referred to as "carbonyl group-containing aliphatic compounds"). In addition, the liquid medium may be a mixed liquid medium composed of two or more types of liquid media.

[0116] Aliphatic and aromatic hydrocarbon compounds include hexane, heptane, octane, cyclohexane, methylcyclohexane, ethylcyclohexane, benzene, ethylbenzene, diethylbenzene, pentylbenzene, isopropylbenzene, toluene, xylene, cymene, and mesitylene.

[0117] Examples of alcohols include methanol, ethanol, isopropanol, butanol, cyclohexanol, phenol, ethylene glycol, diethylene glycol, propylene glycol, and dipropylene glycol.

[0118] Examples of ethers include diethyl ether, tetrahydrofuran, dioxane, anisole, ethylbenzyl ether, crezylmethyl ether, diphenyl ether, dibenzyl ether, phenetol, butylphenyl ether, methyl monoglycidyl ether, ethyl monoglycidyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, and propylene glycol dimethyl ether.

[0119] Examples of esters include cyclohexyl acetate, ethyl 3-ethoxypropionate, dioxane, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol monoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoacetate, diethylene glycol diethyl ether, propylene glycol monoacetate, dipropylene glycol monoacetate, propylene glycol diacetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate.

[0120] Examples of ketones include γ-butyrolactone, acetone, methyl ethyl ketone, 2-heptanone, cycloheptanone, cyclohexanone, methyl-n-pentyl ketone, methyl isobutyl ketone, and methyl isopentyl ketone.

[0121] Examples of nitrogen-containing compounds include dimethylformamide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.

[0122] Examples of sulfur-containing compounds include dimethyl sulfoxide.

[0123] Examples of fluorine-containing compounds include perfluorocarbon, hydrofluoroether, hydrochlorofluorocarbon, hydrofluorocarbon, and fluoropolyether.

[0124] Examples of aqueous media include water and water containing water-soluble organic solvents.

[0125] A water-soluble organic solvent is an organic solvent that is miscible with water in any proportion. As water-soluble organic solvents, the above-mentioned alcohol (excluding ether alcohol), the above-mentioned ether alcohol, and aprotic polar solvents are preferred.

[0126] Examples of non-protonic polar solvents include, for instance, N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran (hereinafter also referred to as "THF"), acetonitrile, acetone, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, 3-methoxy-3-methyl-1-butanol, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0127] As for the water-soluble organic solvent when the liquid medium is an aqueous medium, ether alcohol is preferred because it improves the compatibility between copolymer A and the aqueous medium and makes it easy to form a uniform film on the article, and dipropylene glycol, tripropylene glycol, and dipropylene glycol monomethyl ether are more preferred.

[0128] When the aqueous medium is water containing a water-soluble organic solvent, the content of the water-soluble organic solvent is preferably 1 to 80 parts by mass and more preferably 5 to 60 parts by mass per 100 parts by mass of water.

[0129] The carbonyl group-containing aliphatic compound can be used without practical problems if it is liquid at the temperature at which copolymer A, etc. is dispersed or dissolved, but it is preferable that it be liquid at room temperature. The melting point of the carbonyl group-containing aliphatic compound is preferably 230°C or lower. The molecular structure of the carbonyl group-containing aliphatic compound is not particularly limited, for example, the carbon skeleton may be straight, branched, or cyclic, and may have etheric oxygen between carbon-carbon bonds constituting the main chain or side chain, and may have some of the hydrogen atoms bonded to the carbon atoms substituted with halogen atoms such as fluorine atoms.

[0130] Specific examples of carbonyl group-containing aliphatic compounds include ketones such as cyclic ketones and chain ketones, esters such as chain esters and monoesters of glycols, and carbonates. Among these, cyclic ketones are more preferred. Two or more of these may be used in combination.

[0131] Below, more specific examples of the compounds exemplified above are presented as carbonyl group-containing aliphatic compounds preferably used in the present invention.

[0132] Specific examples of the above-mentioned cyclic ketones include 2-propylcyclopropanone, 2-isopropylcyclopropanone, 2,2,3-trimethylcyclopropanone, 2-ethyl-3-methylcyclopropanone, 2-butylcyclopropanone, 2-isobutylcyclopropanone, 2-tert-butylcyclopropanone, 2-methyl-3-propylcyclopropanone, 2-methyl-3-isopropylcyclopropanone, 2-ethyl-3,3-dimethylcyclopropanone, 2,2,3,3-tetramethylcyclopropanone, 2-pentylcyclopropanone, 2-isopentylcyclopropanone, 2-butyl-3-methylcyclopropanone, 2-ethyl-3-propylcyclopropanone, 2-hexylcyclopropanone, and 2-methyl-3-pentylcyclopropanone. 2-Butyl-3-ethylcyclopropanone, 2,3-Dipropylcyclopropanone, 2-Heptylcyclopropanone, 2-Hexyl-3-methylcyclopropanone, 2-Ethyl-3-Pentylcyclopropanone, 2-Butyl-3-Propylcyclopropanone, 2-Ethylcyclobutanone, 3-Ethylcyclobutanone, 2,2-Dimethylcyclobutanone, 2,3-Dimethylcyclobutanone, 3,3-Dimethylcyclobutanone, 2,4-Dimethylcyclobutanone, 2-Propylcyclobutanone, 3-Propylcyclobutanone, 2-Isopropylcyclobutanone, 3-Isopropylcyclobutanone, 2,2,3-Trimethylcyclobutanone, 2,3,3-Trimethylcyclobutanone, 2,3,4-Trimethylcyclobutanone, 2,2,4-Trimethylcyclobutanone, 2-Butylcyclobutanone, 2-Isobutylcyclobutanone, 2-tert-butylcyclobutanone, 3-Butylcyclobutanone, 3-Isobutylcyclobutanone, 3-tert-butylcyclobutanone, 2-Pentylcyclobutanone, 3-Pentylcyclobutanone, 2-Isopentylcyclobutanone, 3-Isopentylcyclobutanone, 2-Hexylcyclobutanone, 3-Hexylcyclobutanone, 2-Methylcyclopentanone, 3-Methylcyclopentanone, 2-Ethylcyclopentanone, 3-Ethylcyclopentanone, 2,2-Dimethylcyclopentanone, 2,3-Dimethylcyclopentanone, 3,3-Dimethylcyclopentanone, 2,5-Dimethylcyclopentanone, 2,4-Dimethylcyclopentanone, 3,4-Dimethylcyclopentanone, 2-Propylcyclopentanone, 2-Isopropylcyclopentanone, 3-Propylcyclopentanone, 3-Isopropylcyclopentanone, 2,2,5-Trimethylcyclopentanone,2-Butylcyclopentanone, 2-Isobutylcyclopentanone, 2-tert-butylcyclopentanone, 3-butylcyclopentanone, 3-Isobutylcyclopentanone, 3-tert-butylcyclopentanone, 2,2,5,5-tetramethylcyclopentanone, 2-pentylcyclopentanone, 2-isopentylcyclopentanone, 3-pentylcyclopentanone, 3-isopentylcyclopentanone, cyclohexanone, 2-methylcyclohexanone, 3-methylcyclohexanone, 4-methylcyclopentanone, 2-ethylcyclohexanone, 3-ethylcyclohexanone, 4-ethylcyclohexanone, 2,2-dimethylcyclohexanone, 2,3-dimethylcyclohexanone, 2,4-dimethylcyclohexanone, 2,5-Dimethylcyclohexanone, 2,6-Dimethylcyclohexanone, 2-Propylcyclohexanone, 2-Isopropylcyclohexanone, 3-Propylcyclohexanone, 3-Isopropylcyclohexanone, 4-Propylcyclohexanone, 4-Isopropylcyclohexanone, 2,2,6-Trimethylcyclohexanone, 2,2,4-Trimethylcyclohexanone, 2,4,4-Trimethylcyclohexanone, 3,3,5-Trimethylcyclohexanone, 2,4,6-Trimethylcyclohexanone, 2-Butylcyclohexanone, 2-Isobutylcyclohexanone, 2-tert-Butylcyclohexanone, 3-Butylcyclohexanone, 3-Isobutylcyclohexanone, 3-tert-Butylcyclohexanone, 4-Butylcyclohexanone, 4-Isobutylcyclohexanone, 4-tert-butylcyclohexanone, 2,2-Diethylcyclohexanone, 2,4-Diethylcyclohexanone, 2,6-Diethylcyclohexanone, 3,5-Diethylcyclohexanone, 2,2,6,6-Tetramethylcyclohexanone, Cycloheptanone, 2-Methylcycloheptanone, 3-Methylcycloheptanone, 4-Methylcycloheptanone, 2-Ethylcycloheptanone, 3-Ethylcycloheptanone, 4-Ethylcycloheptanone, 2,2-Dimethylcycloheptanone, 2,7-Dimethylcycloheptanone, 2-Profilcycloheptanone, 2-Isopropylcycloheptanone, 3-Profilcycloheptanone, 3-Isopropylcycloheptanone, 4-propylcycloheptanone, 4-isopropylcycloheptanone, 2,2,7-trimethylcycloheptanone, cyclooctanone, 2-methylcyclooctanone, 3-methylcyclooctanone, 4-methylcyclooctanone, 5-methylcyclooctanone, 2-ethylcyclooctanone, 3-ethylcyclooctanone,Examples include 4-ethylcyclooctanone, 5-ethylcyclooctanone, 2,2-dimethylcyclooctanone, 2,8-dimethylcyclooctanone, cyclononanone, 2-methylcyclononanone, 3-methylcyclononanone, 4-methylcyclononanone, 5-methylcyclononanone, cyclodecanone, isophorone, (-)-fenchone((1R,4S)-1,3,3-trimethylbicyclo[2.2.1]heptan-2-one), (+)-fenchone((1S,4R)-1,3,3-trimethylbicyclo[2.2.1]heptan-2-one)), etc.

[0133] Specific examples of the above-mentioned chain-type ketones include 2-hexanone, 3-hexanone, methylisobutylketone, ethylisopropylketone, 3,3-dimethyl-2-butanone, 2-heptanone, 3-heptanone, 4-heptanone, diisopropylketone, 5-methyl-2-hexanone, 2-octanone, 3-octanone, 4-octanone, 5-methyl-3-heptanone, 2-nonanone, 3-nonanone, 4-nonanone, 5-nonanone, diisobutylketone, 2-decanone, 3-decanone, 4-decanone, 5-decanone, etc.

[0134] Specific examples of the above-mentioned chain-type esters include pentyl formate, isopentyl formate, cyclopentyl formate, hexyl formate, cyclohexyl formate, heptyl formate, octyl formate, 2-ethylhexyl formate, nonyl formate, butyl acetate, isobutyl acetate, sec-butyl acetate, tert-butyl acetate, pentyl acetate, isopentyl acetate, cyclopentyl acetate, hexyl acetate, cyclohexyl acetate, heptyl acetate, octyl acetate, 2-ethylhexyl acetate, propyl propionate, isopropyl propionate, butyl propionate, isobutyl propionate, sec-butyl propionate, tert-butyl propionate, pentyl propionate, isopentyl propionate, cyclopentyl propionate, hexyl propionate. Cyclohexyl propionate, heptyl propionate, 2,2,3,3,3-pentafluoropropyl propionate, 2,2,3,3-tetrafluoropropyl propionate, ethyl butyrate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, sec-butyl butyl butyrate, tert-butyl butyrate, pentyl butyrate, isopentyl butyrate, cyclopentyl butyrate, hexyl butyrate, cyclohexyl butyrate, 2,2,2-trifluoroethyl butyrate, 2,2,3,3,3-pentafluoropropyl butyrate, 2,2,3,3-tetrafluoropropyl butyrate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, butyl isobutyrate, isobutyl isobutyl isobutyl isobutyl sec-butyl isobutyrate, tert-butyl isobutyrate, pentyl isobutyrate, isopentyl isobutyrate, cyclopentyl isobutyrate, hexyl isobutyrate, cyclohexyl isobutyrate, 2,2,2-trifluoroethyl isobutyrate, 2,2,3,3,3-pentafluoropropyl isobutyrate, 2,2,3,3-tetrafluoropropyl isobutyrate, methyl valerate, ethyl valerate, propyl valerate, isopropyl valerate, butyl valerate, isobutyl valerate, sec-butyl valerate, tert-butyl valerate, pentyl valerate, isopentyl valerate, 2,2,2-trifluoroethyl valerate, 2,2,3,3,3-pentafluoropropyl valerate, 2,2,3,3-tetrafluoropropyl valerate, Methyl isovalerate, ethyl isovalerate, propyl isovalerate,Isopropyl isovalerate, butyl isovalerate, isobutyl isovalerate, sec-butyl isovalerate, tert-butyl isovalerate, pentyl isovalerate, isopentyl isovalerate, 2,2,2-trifluoroethyl isovalerate, 2,2,3,3,3-pentafluoropropyl isovalerate, 2,2,3,3-tetrafluoropropyl isovalerate, methyl pivalate, ethyl pivalate, propyl pivalate, isopropyl pivalate, butyl pivalate, isobutyl pivalate, sec-butyl pivalate, tert-butyl pivalate, pentyl pivalate, isopentyl pivalate, 2,2,2-trifluoroethyl pivalate, 2,2,3,3,3-pentafluoropropyl pivalate, 2,2,3,3-tetrafluoropropyl pivalate, Methyl hexanoate, ethyl hexanoate, propyl hexanoate, isopropyl hexanoate, butyl hexanoate, isobutyl hexanoate, sec-butyl hexanoate, tert-butyl hexanoate, 2,2,2-trifluoroethyl hexanoate, 2,2,3,3,3-pentafluoropropyl hexanoate, 2,2,3,3-tetrafluoropropyl hexanoate, methyl heptanoate, ethyl heptanoate, propyl heptanoate, isopropyl heptanoate, 2,2,2-trifluoroethyl heptanoate, 2,2,3,3,3-pentafluoropropyl heptanoate, 2,2,3,3-tetrafluoropropyl heptanoate, methyl cyclohexanecarboxylate, ethyl cyclohexanecarboxylate, propyl cyclohexanecarboxylate, isopropyl cyclohexanecarboxylate, 2,2,2-trifluoroethyl cyclohexanecarboxylate, 2,2,3,3,3-pentafluoropropyl cyclohexanecarboxylic acid, 2,2,3,3-tetrafluoropropyl cyclohexanecarboxylic acid, methyl octanoate, ethyl octanoate, 2,2,2-trifluoroethyl octanoate, methyl nonanoate, butyl trifluoroacetate, pentyl trifluoroacetate, hexyl trifluoroacetate, heptyl trifluoroacetate, octyl trifluoroacetate, propyl pentafluoropropionate, butyl pentafluoropropionate, pentyl pentafluoropropionate, hexyl pentafluoropropionate, heptyl pentafluoropropionate, ethyl perfluorobutanoate, propyl perfluorobutanoate, butyl perfluorobutanoate, pentyl perfluorobutanoate, hexyl perfluorobutanoate, methyl perfluoropentanoate, ethyl perfluoropentanoate, propyl perfluoropentanoate, butyl perfluoropentanoate,Examples include pentyl perfluoropentanoic acid, methyl perfluorohexanoate, ethyl perfluorohexanoate, propyl perfluorohexanoate, butyl perfluorohexanoate, methyl perfluoroheptanoate, ethyl perfluoroheptanoate, propyl perfluoroheptanoate, methyl perfluorooctanoate, ethyl perfluorooctanoate, etc.

[0135] Specific examples of the monoesters of the above glycols include 2-ethoxyethyl acetate, 2-propoxyethyl acetate, 2-butoxyethyl acetate, 2-pentyloxyethyl acetate, 2-hexyloxyethyl acetate, 1-methoxy-2-acetoxypropane, 1-ethoxy-2-acetoxypropane, 1-propoxy-2-acetoxypropane, 1-butoxy-2-acetoxypropane, 1-pentyloxy-2-acetoxypropane, 3-methoxybutyl acetate, 3-ethoxybutyl acetate, 3-propoxybutyl acetate, 3-butoxybutyl acetate, 3-methoxy-3-methylbutyl acetate, 3-ethoxy-3-methylbutyl acetate, 3-propoxy-3-methylbutyl acetate, 4-methoxybutyl acetate. Examples include 4-ethoxybutyl acetate, 4-propoxybutyl acetate, and 4-butoxybutyl acetate.

[0136] Specific examples of the above carbonates include butylmethyl carbonate, ethylpropyl carbonate, dipropyl carbonate, diisopropyl carbonate, butylpropyl carbonate, butylisopropyl carbonate, isobutylpropyl carbonate, tert-butylpropyl carbonate, tert-butylisopropyl carbonate, dibutyl carbonate, diisobutyl carbonate, ditert-butyl carbonate, bis(2,2,3,3,3-pentafluoropropyl)carbonate, bis(2,2,3,3-tetrafluoropropyl)carbonate, bis(1,1,1,3,3,3-hexafluoroisopropyl)carbonate, bis(2,2,3,3,4,4,4-heptafluorobutyl)carbonate, bis(perfluoro-tert-butyl)carbonate, etc.

[0137] The total content (polymer concentration) of copolymer A and other polymers contained as necessary in the primer layer forming composition is more preferably 5 to 70 mass%, more preferably 7 to 60 mass%, and particularly preferably 9 to 55 mass% with respect to the total amount of the primer layer forming composition. If it is above the lower limit of the above range, the adhesion to the current collector and the electrode active material layer is excellent. If it is below the upper limit of the above range, the conductivity is improved, and the function as a battery is improved.

[0138] The solid content of the primer layer-forming composition is more preferably 1 to 50 mass% with respect to the total amount of the primer layer-forming composition, more preferably 3 to 40 mass%, and particularly preferably 5 to 30 mass%, in that the primer layer-forming composition can be applied thinly.

[0139] When the composition for forming a primer layer includes a conductive material, the solid content concentration of the composition for forming a primer layer is more preferably 3 to 60 mass% and even more preferably 5 to 50 mass% with respect to the total amount of the composition for forming a primer layer. In this case, the polymer concentration in the composition for forming a primer layer is more preferably 3 to 60 mass% and even more preferably 5 to 50 mass% with respect to the total amount of solids.

[0140] <Electrode Composite for Capacitor Devices>

[0141] The electrode composite for obtaining an electrode for a capacitor device according to the present invention (hereinafter also simply referred to as "electrode composite") contains a binder and an electrode active material. If necessary, it may contain a conductive material and other components other than these.

[0142] The binder used in the present invention is not particularly limited and known binders may be appropriately used. Among these, a binder in which at least a portion of the polymer component is a fluorine-containing polymer is preferred because the utility of the effect obtained by the primer of the present invention is high.

[0143] The binder used in the present invention preferably contains the copolymer A, just like the primer of the present invention.

[0144] A preferred embodiment of the binder used in the present invention is the same as a preferred embodiment of the primer of the present invention.

[0145] The electrode active material used in the present invention is not particularly limited, and known materials may be appropriately used.

[0146] MnO2, V2O5, and V6O are used as positive electrode active materials. 13 Metal oxides such as TiS2, MoS2, FeS, metal sulfides such as LiCoO2, LiNiO2, LiMn2O4, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples include lithium complex metal oxides containing transition metals such as Co, Ni, Mn, Fe, and Ti, such as O2 and LiFePO4, and compounds in which some of the transition metal elements in these compounds are substituted with other metal elements. Additionally, conductive polymer materials such as polyacetylene and poly-p-phenylene may be used. Furthermore, materials coated with carbon materials or inorganic compounds on part or the entire surface of these may also be used.

[0147] Examples of negative electrode active materials include carbonaceous materials such as coke, graphite, mesophase pitch spheres, carbides of polymer compounds like phenolic resin and polyparaphenylene, vapor-phase carbon fibers, and carbon fibers. In addition, metals such as Si, Sn, Sb, Al, Zn, and W that can be alloyed with lithium can also be mentioned, such as, for example, silicon monoxide with the general formula SiO₂. x Examples of silicon oxide can be represented as (where x is preferably 0.5 to 1.5). The electrode active material may also be one in which a conductive material is attached to the surface by mechanical modification or the like.

[0148] In the case of electrode composites for lithium-ion secondary batteries, the electrode active material used must be capable of reversibly inserting and releasing lithium ions by applying a potential in the electrolyte, and can be an inorganic compound or an organic compound.

[0149] In particular, it is desirable to include a conductive material in the electrode composite used for manufacturing the positive electrode. By including a conductive material, electrical contact between electrode active materials is improved, and electrical resistance within the active material layer can be lowered, thereby improving the discharge rate characteristics of the non-aqueous secondary battery.

[0150] Examples of conductive materials include conductive carbons such as acetylene black, ketjen black, carbon black, graphite, vapor-grown carbon fibers, and carbon nanotubes.

[0151] It is desirable for the electrode composite to contain a conductive material, as the addition of a small amount of the conductive material significantly increases the effect of reducing electrical resistance.

[0152] In addition to the above, known components in electrode composites may be used. Specific examples include water-soluble polymers such as carboxymethylcellulose, polyvinyl alcohol, polyacrylic acid, and polymethacrylic acid.

[0153] The ratio of the total polymer (copolymer A and, if necessary, the total of other polymers contained) in the electrode composite is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and particularly preferably 1 to 8 parts by mass, per 100 parts by mass of the electrode active material.

[0154] In addition, when the electrode composite contains a conductive material, the proportion of the conductive material in the electrode composite is preferably greater than 0 parts by mass and less than or equal to 20 parts by mass with respect to 100 parts by mass of the electrode active material, more preferably 1 to 10 parts by mass, and particularly preferably 3 to 8 parts by mass.

[0155] When the electrode mixture contains a liquid medium, the solid content concentration in the electrode mixture is preferably 30 to 95 mass%, more preferably 35 to 90 mass%, and particularly preferably 40 to 85 mass%.

[0156] <Electrode for Capacitor Devices>

[0157] The electrode for a capacitor device according to the present invention is an electrode for a capacitor device having a current collector and an electrode active material layer formed on the current collector, and has a primer layer comprising a primer for a capacitor device electrode according to the present invention between the current collector and the electrode active material layer.

[0158] As for the current collector, it is not particularly limited as long as it is made of a conductive material, but generally, examples include metal foils such as aluminum, nickel, stainless steel, and copper, metal networks, and metal porous bodies. Aluminum is preferably used as the positive electrode current collector, and copper is preferably used as the negative electrode current collector. The thickness of the current collector is preferably 1 to 100 μm.

[0159] An electrode for a capacitor device is obtained by forming a primer layer using copolymer A, which is the primer of the present invention, on at least one side, preferably both sides, of a current collector, and then forming an electrode active material layer on the primer layer using an electrode composite.

[0160] A primer layer is obtained, for example, by applying the primer-forming composition of the present invention to at least one side, preferably both sides, of a current collector, and removing the liquid medium in the primer composition by drying. If necessary, the primer layer after drying may be pressed to form it into a desired thickness.

[0161] In addition, a primer layer can be formed without using a liquid medium by using a powder composed of particles of copolymer A, which is the primer of the present invention.

[0162] There is no particular limitation on the thickness of the primer layer, but it is preferably 0.1 to 100 μm, and more preferably 0.5 to 50 μm.

[0163] If the thickness of the primer layer is greater than or equal to the lower limit of a desirable range, the adhesion of the electrode mixture to the current collector is excellent. If the thickness of the primer layer is less than or equal to the upper limit of a desirable range, conductivity is improved, and the function as a battery is enhanced.

[0164] The electrode active material layer is obtained, for example, by applying an electrode composite containing a liquid medium onto a primer layer formed on a current collector, and removing the liquid medium by drying. If necessary, the electrode active material layer after drying may be pressed to form it to a desired thickness. Alternatively, the electrode active material layer may be formed without using a liquid medium by using a powdered electrode composite that does not contain a liquid medium.

[0165] The coating amount of the electrode mixture containing a liquid medium, converted to a solid content, is preferably 1 to 3000 g / m², and more preferably 5 to 1000 g / m². The function as a battery is improved when the coating amount of the electrode mixture is above the lower limit of the preferred range. The battery size can be reduced when the coating amount of the electrode mixture is below the upper limit of the preferred range.

[0166] The thickness of the electrode active material layer is preferably 1 to 500 μm, and more preferably 5 to 300 μm. The function as a battery is improved when the thickness of the electrode active material layer is greater than or equal to the lower limit of the preferred range. The battery size can be reduced when the thickness of the electrode active material layer is less than or equal to the upper limit of the preferred range.

[0167] Various coating methods can be used to apply the electrode mixture containing a primer layer-forming composition and a liquid medium. Examples include the doctor blade method, dip method, reverse roll method, direct roll method, gravure method, extrusion method, and brush coating method. Although there are no specific limitations on the coating temperature, a temperature near room temperature is generally preferred. Drying can be performed using various drying methods, such as drying with warm air, hot air, low-humidity air, vacuum drying, or drying by irradiation with (far) infrared rays or electron beams. Although there are no specific limitations on the drying temperature, in the case of a heated vacuum dryer, a temperature of room temperature to 200°C is generally preferred. For the pressing method, a mold press or a roll press can be used.

[0168] In the case of the primer of the present invention that does not contain a liquid medium, a powder composed of particles of copolymer A, which is the primer, is placed on a current collector, and a primer layer is formed by calendering. Alternatively, a film for forming an undercoat layer may be produced by calendering, and then laminated onto a current collector.

[0169] In the case where the binder for the capacitor device is a dry binder that does not contain a liquid medium, the electrode mixture can be placed on a primer layer formed on a current collector and an electrode can be formed by calendering. Alternatively, an electrode film can be produced by calendering the electrode mixture and then laminated onto a primer layer formed on a current collector.

[0170] <Capacitor Device>

[0171] A capacitor device using the primer composition for a capacitor device electrode and the electrode for a capacitor device according to the present invention has at least one pair of electrodes and an electrolyte interposed between the pair of electrodes. In addition, when the electrolyte is in a liquid state, it is preferable to have a separator.

[0172] Examples of energy storage devices include, but are not particularly limited, batteries, electrochemical sensors, electrochromic elements, electrochemical switching elements, electrolytic capacitors, and electrochemical capacitors.

[0173] As for the battery, it is not particularly limited as long as it has electrodes and an electrolyte, but examples include alkali metal batteries, alkali metal ion batteries, alkaline earth metal ion batteries, radical batteries, solar cells, and fuel cells.

[0174] In a preferred embodiment, the battery is, in particular, an alkali metal battery, an alkali metal ion battery, or an alkaline earth metal battery, and may be, for example, a lithium battery, a lithium ion battery, a sodium ion battery, a magnesium battery, a lithium air battery, a sodium sulfur battery, or a lithium sulfur battery, and preferably a lithium ion battery. The battery may be a primary battery or a secondary battery, and it is preferred to be a secondary battery.

[0175] The present invention is a secondary battery comprising an electrode and an electrolyte for the above-mentioned storage device. Preferably, the secondary battery is an alkali metal ion secondary battery, and in particular, a lithium ion secondary battery.

[0176] The following describes lithium-ion secondary batteries in detail.

[0177] <Lithium-ion secondary battery>

[0178] A lithium-ion secondary battery as a storage device comprises an electrode for a storage device according to the present invention as at least one of a positive electrode and a negative electrode, and also comprises an electrolyte. In addition, if the electrolyte is in a liquid state, it is preferable to provide a separator.

[0179] The electrolyte comprises an electrolyte and a solvent. As the solvent, non-protonic organic solvents are used, for example, alkyl carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and methyl ethyl carbonate (MEC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfolane; and sulfur-containing compounds such as dimethyl sulfoxide. In particular, dimethyl carbonate, ethylene carbonate, propylene carbonate, diethyl carbonate, and methyl ethyl carbonate are preferred because they allow for easy attainment of high ionic conductivity and have a wide operating temperature range. These may be used individually or in a mixture of two or more.

[0180] Examples of lithium salts that can be used as electrolytes include LiClO4, LiBF4, LiPF6, LiAsF5, CF3SO3Li, (CF3SO2)2NLi, and (FSO2)2NLi.

[0181] Solid Electrolytes

[0182] In the battery of the present disclosure, a solid electrolyte may be used instead of the liquid electrolyte described above. Examples of solid electrolytes include inorganic electrolytes and organic electrolytes.

[0183] Examples of inorganic electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes.

[0184] Examples of oxide-based solid electrolytes include perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, and garnet-type oxides.

[0185] Sulfide-based solid electrolytes include, for example, Li2S-P2S5 compounds, Li2S-SiS2 compounds, Li2S-GeS2 compounds, Li2S-B2S3 compounds, Li2S-P2S3 compounds, LiI-Si2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 10 GeP2S 12 ...can be cited.

[0186] Examples of hydride-based solid electrolyte materials include LiBH4, LiBH4-3KI, LiBH4-PI2, LiBH4-P2S5, LiBH4-LiNH2, 3LiBH4-LiI, LiNH2, Li2AlH6, Li(NH2)2I, Li2NH, LiGd(BH4)3Cl, Li2(BH4)(NH2), Li3(NH2)I, and Li4(BH4)(NH2)3.

[0187] Examples of organic electrolytes include polymer-based solid electrolytes.

[0188] Examples of polymer-based solid electrolytes include organic polymer electrolytes such as polymer compounds containing one or more selected from the group consisting of polyoxyethylene-based polymer compounds, polyorganosiloxane chains, and polyoxyalkylene chains.

[0189] Examples

[0190] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Tests and evaluations in the examples and comparative examples were carried out in the following manner. Additionally, Examples 1 to 8 are examples, and Examples 9 and 10 are comparative examples.

[0191] <Measurement Method>

[0192] [Melting Point (°C)]

[0193] It was obtained from the endothermic peak when heated to 300 ℃ at 10 ℃ / min in an air atmosphere using a scanning differential thermal analyzer (DSC7200 manufactured by SII).

[0194] [Average particle size and D90 of the powder]

[0195] A laser diffraction and scattering particle size distribution measuring device (LA-920 measuring instrument) manufactured by Horiba Manufacturing Co., Ltd. was used to disperse the powder in water, measure the particle size distribution, and calculate the average particle size (㎛) and D90 (㎛).

[0196] [Small Packing Volume Density and Close Packing Volume Density]

[0197] The small packing volume density and dense packing volume density of the powder were measured using the method described in

[0117] and

[0118] of International Publication No. 2016 / 017801.

[0198] [Acid anhydride content (mol%)]

[0199] Using a 200 µm thick film obtained by press molding a fluorine-containing polymer, at 1800–1900 cm by a Fourier transform infrared spectrometer (manufactured by Thermo Fisher Scientific, Nicolet iS10) -1 The intensity of absorption originating from acid anhydride groups appearing nearby was measured, and the acid anhydride content (the ratio of units having acid anhydride groups among the total units constituting the fluorinated polymer) was calculated.

[0200] [MFR (Melt Flow Rate)]

[0201] Using a melt indexer (manufactured by Decknoseven Co., Ltd.), the mass (g) of copolymer flowing out in 10 minutes from an orifice with a diameter of 2 mm and a length of 8 mm under a load of 49 N in accordance with ASTM D3159 was measured and recorded as MFR (g / 10 min). 220 °C, 297 °C, or 380 °C was used as the measurement temperature.

[0202] <Copolymer used in primer>

[0203] The following copolymer was used to form a primer layer in the form of a powder or dispersion.

[0204] · Copolymer A-1: ​​A copolymer obtained by polymerizing TFE, CF2=CF-O-(CF2)3F, and NAH in the same manner as in Example 5 of WO2015 / 182702 (melting point: 300 °C, MFR 25 g / 10 min at 380 °C).

[0205] · Copolymer A-2: A copolymer obtained by polymerizing TFE, ethylene, CH2=CH(CF2)2F, and IAH in the same manner as in Example 2 of WO2015 / 182702 (melting point: 255 °C, MFR 26 g / 10 min at 297 °C).

[0206] · Copolymer A-3: A copolymer obtained by polymerizing TFE, ethylene, HFP, CH2=CH(CF2)4F, and IAH in the same manner as in Example 3 of WO2015 / 182702 (melting point: 183 °C, MFR 11 g / 10 min at 220 °C).

[0207] [Copolymer A-1 (Powder)]

[0208] Copolymer A-1 was ground using a jet mill (manufactured by Seishin Enterprise, single-truck jet mill type FS-4) under conditions of a grinding pressure of 0.5 MPa and a processing speed of 1 kg / hr to obtain copolymer A-1 (powder).

[0209] The average particle size of the obtained copolymer A-1 (powder) was 2.58 μm, D90 was 7.1 μm, the small packing bulk density was 0.278 g / mL, and the dense packing bulk density was 0.328 g / mL.

[0210] [Copolymer A-2 (Powder)]

[0211] Copolymer A-2 was ground under the same conditions as copolymer A-1 to produce copolymer A-2 (powder).

[0212] The average particle size of the obtained copolymer A-2 (powder) was 3.54 μm, D90 was 9.2 μm, the small packing bulk density was 0.332 g / mL, and the dense packing bulk density was 0.395 g / mL.

[0213] [Copolymer A-3 (Powder)]

[0214] Copolymer A-3 was ground under the same conditions as copolymer A-1 to produce copolymer A-3 (powder).

[0215] The average particle size of the obtained copolymer A-3 (powder) was 2.92 μm, D90 was 8.2 μm, the small packing bulk density was 0.313 g / mL, and the dense packing bulk density was 0.388 g / mL.

[0216] [Copolymer A-3 (DIPK dispersion)]

[0217] 50 g of copolymer A-3 (powder) and 450 g of diisopropyl ketone (DIPK) were placed in a 1 L glass pressure reaction vessel equipped with a stirrer, heated to 150 ℃, and stirred for 1 hour to disperse copolymer A-3 (powder). Afterward, the mixture was cooled to room temperature while stirring to obtain copolymer A-3 (DIPK dispersion).

[0218] <Example 1>

[0219] (Composition for forming a primer layer 1)

[0220] Composition 1 for forming a primer layer in which copolymer A-1 is dispersed in water was prepared by mixing each of the following components in a ball mill for 5 hours.

[0221] · Carbon powder (specific surface area; 150 m² / g): 40 parts by mass

[0222] · Copolymer A-1 (powder): 40 parts by mass

[0223] · Non-ionic surfactant (manufactured by Neos, Ptergent 250): 3 parts by mass

[0224] · Distilled water: 320 parts by mass

[0225] (Preparation of electrolyte)

[0226] An electrolyte was obtained by adding LiPF6 to a mixed solvent (30:70 volume ratio) of ethylene carbonate, a high dielectric constant solvent, and ethylmethyl carbonate, a low viscosity solvent, at a concentration of 1.0 mol / liter.

[0227] (Fabrication of positive electrode laminate and positive electrode)

[0228] LiNi as a positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 A positive electrode composite slurry was prepared by using O2, carbon black as a conductive material, and an N-methyl-2-pyrrolidone dispersion of polyvinylidene fluoride (PVdF) as a binder, and mixing the active material, conductive material, and binder such that the solid content ratio is 92 / 3 / 5 (mass % ratio).

[0229] Composition 1 was applied to an aluminum foil current collector with a thickness of 20 μm to a dry thickness of 10 μm and dried, and further, the obtained positive electrode composite slurry was applied to the substrate to a dry thickness of 100 μm and dried, and then compression molded by a press machine to form a positive electrode laminate. The positive electrode laminate was punched out to a diameter of 1.6 cm using a punching machine to produce a circular positive electrode.

[0230] (Fabrication of negative electrode laminates and negative electrodes)

[0231] Artificial graphite powder and amorphous silicon (SiO) were used as negative electrode active materials, an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose 1 mass%) was used as a thickener, and an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber 50 mass%) was used as a binder, and a negative electrode composite slurry was prepared by mixing the active materials, thickener, and binder in a solid content ratio of 93 / 4.6 / 1.2 / 1.2 (mass% ratio).

[0232] Composition 1 was applied to a copper foil with a thickness of 20 μm to a dry thickness of 10 μm and dried, and furthermore, the obtained negative electrode composite slurry was applied to the copper foil to a dry thickness of 100 μm and dried, and then compression molded by a press machine to form a negative electrode laminate. The negative electrode laminate was punched out to a diameter of 1.6 cm using a punching machine to produce a circular negative electrode.

[0233] (Production of lithium-ion secondary batteries)

[0234] The above circular positive and negative electrodes were placed facing each other with a 20 μm thick microporous polyethylene film (separator) interposed and accommodated in a pouch. The electrolyte obtained above was injected into this pouch, and after the electrolyte sufficiently penetrated the separator, etc., the pouch was sealed and pre-charged and aged to produce a coin-type lithium-ion secondary battery.

[0235] <Example 2>

[0236] (Composition for forming a primer layer 2)

[0237] Composition 2 for forming a primer layer in which copolymer A-1 is dispersed in N-methylpyrrolidone (NMP) was prepared by mixing each of the following components in a ball mill for 5 hours.

[0238] · Carbon powder (specific surface area; 150 m² / g): 40 parts by mass

[0239] · Copolymer A-1 (powder): 40 parts by mass

[0240] · Non-ionic surfactant (manufactured by Neos, FTX-218P): 3 parts by mass

[0241] ·NMP: 320 parts by mass

[0242] (Fabrication of positive electrode laminate and positive electrode)

[0243] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 1, except that the above composition 2 was used instead of the above composition 1.

[0244] (Fabrication of negative electrode laminates and negative electrodes)

[0245] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 1, except that the above composition 2 was used instead of the above composition 1.

[0246] (Production of lithium-ion secondary batteries)

[0247] A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the positive and negative electrodes obtained in Example 2 were used.

[0248] <Example 3>

[0249] (Composition for forming a primer layer 3)

[0250] Composition 3 for forming a powdered primer layer using copolymer A-1 was prepared by mixing each of the following components with a Henschel mixer.

[0251] · Carbon powder (specific surface area; 150 m² / g): 40 parts by mass

[0252] · Fluoropolymer-containing copolymer (A) powder: 40 parts by mass

[0253] (Preparation of electrolyte)

[0254] An electrolyte was obtained by adding LiPF6 to a mixed solvent (30:70 volume ratio) of ethylene carbonate, a high dielectric constant solvent, and ethylmethyl carbonate, a low viscosity solvent, at a concentration of 1.0 mol / liter.

[0255] (Fabrication of positive electrode laminate and positive electrode)

[0256] A positive electrode composite slurry was prepared in the same manner as in Example 1.

[0257] By calendering the obtained composition 3, a film for forming an underlayer with a thickness of 10 μm was produced. The film for forming the underlayer was laminated onto an aluminum foil current collector with a thickness of 20 μm, and furthermore, the obtained positive electrode composite slurry was applied to the surface to a dry thickness of 100 μm and dried, and then compression molded using a press machine to form a positive electrode laminate. The positive electrode laminate was punched out to a diameter of 1.6 cm using a punching machine to produce a circular positive electrode.

[0258] (Fabrication of negative electrode laminates and negative electrodes)

[0259] A negative electrode composite slurry was prepared in the same manner as in Example 1.

[0260] By calendering the obtained composition 3, a film for forming an underlayer with a thickness of 10 μm was produced. The film for forming an underlayer was laminated onto a copper foil with a thickness of 20 μm, and furthermore, the obtained negative electrode composite slurry was applied to the surface to a dry thickness of 100 μm and dried, and then compression molded using a press machine to form a negative electrode laminate. The negative electrode laminate was punched out to a diameter of 1.6 cm using a puncher to produce a circular negative electrode material.

[0261] (Production of lithium-ion secondary batteries)

[0262] A lithium-ion secondary battery was manufactured in the same manner as in Example 1, except that the positive and negative electrodes obtained in Example 3 were used.

[0263] <Example 4>

[0264] (Composition for forming a primer layer 4)

[0265] Composition 4 for forming a primer layer in which copolymer A-2 is dispersed in water was prepared in the same manner as in Example 1, except that copolymer A-2 (powder) was used instead of copolymer A-1 (powder).

[0266] (Fabrication of positive electrode laminate and positive electrode)

[0267] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 1, except that the above composition 4 was used instead of the above composition 1.

[0268] (Fabrication of negative electrode laminates and negative electrodes)

[0269] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 1, except that the above composition 4 was used instead of the above composition 1.

[0270] (Production of lithium-ion secondary batteries)

[0271] A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the positive and negative electrodes obtained in Example 4 were used.

[0272] <Example 5>

[0273] (Composition for forming a primer layer 5)

[0274] Composition 5 for forming a powder-type primer layer using copolymer A-2 was prepared in the same manner as in Example 3, except that copolymer A-2 (powder) was used instead of copolymer A-1 (powder).

[0275] (Fabrication of positive electrode laminate and positive electrode)

[0276] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 3, except that the above composition 5 was used instead of the above composition 3.

[0277] (Fabrication of negative electrode laminates and negative electrodes)

[0278] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 3, except that the above composition 5 was used instead of the above composition 3.

[0279] (Production of lithium-ion secondary batteries)

[0280] A lithium-ion secondary battery was manufactured in the same manner as in Example 3, except that the positive and negative electrodes obtained in Example 5 were used.

[0281] <Example 6>

[0282] (Composition for forming a primer layer 6)

[0283] Composition 6 for forming a primer layer in which copolymer A-3 is dispersed in water was prepared in the same manner as in Example 1, except that copolymer A-3 (powder) was used instead of copolymer A-1 (powder).

[0284] (Fabrication of positive electrode laminate and positive electrode)

[0285] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 1, except that the above composition 6 was used instead of the above composition 1.

[0286] (Fabrication of negative electrode laminates and negative electrodes)

[0287] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 1, except that the above composition 6 was used instead of the above composition 1.

[0288] (Production of lithium-ion secondary batteries)

[0289] A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the positive and negative electrodes obtained in Example 6 were used.

[0290] <Example 7>

[0291] (Composition for forming a primer layer 7)

[0292] Composition 7 for forming a primer layer in which copolymer A-3 is dispersed in diisopropyl ketone (DIPK) was prepared by mixing each of the following components in a ball mill for 5 hours.

[0293] · Carbon powder (specific surface area; 150 m² / g): 10 parts by mass

[0294] · Copolymer A-3 (DIPK dispersion): 100 parts by mass

[0295] (Fabrication of positive electrode laminate and positive electrode)

[0296] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 1, except that the above composition 7 was used instead of the above composition 1.

[0297] (Fabrication of negative electrode laminates and negative electrodes)

[0298] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 1, except that the above composition 7 was used instead of the above composition 1.

[0299] (Production of lithium-ion secondary batteries)

[0300] A lithium-ion secondary battery was manufactured in the same manner as in Example 1, except that the positive and negative electrodes obtained in Example 7 were used.

[0301] <Example 8>

[0302] (Composition for forming a primer layer 8)

[0303] Composition 8 for forming a powder-type primer layer using copolymer A-3 was prepared in the same manner as in Example 3, except that copolymer A-3 (powder) was used instead of copolymer A-1 (powder).

[0304] (Fabrication of positive electrode laminate and positive electrode)

[0305] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 3, except that the above composition 8 was used instead of the above composition 3.

[0306] (Fabrication of negative electrode laminates and negative electrodes)

[0307] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 3, except that the above composition 8 was used instead of the above composition 3.

[0308] (Production of lithium-ion secondary batteries)

[0309] A lithium-ion secondary battery was manufactured in the same manner as in Example 3, except that the positive and negative electrodes obtained in Example 8 were used.

[0310] <Example 9>

[0311] (Composition for forming a primer layer 9)

[0312] Composition 9 for forming a polyurethane-based primer layer was prepared by mixing each of the following components in a ball mill for 5 hours.

[0313] · Carbon powder (specific surface area; 150 m² / g): 30 parts by mass

[0314] · Polyurethane (Miractran P490, manufactured by Miractran Co., Ltd., Japan): 65 parts by mass

[0315] · Polyisocyanate (Coronate L, manufactured by Tosos): 5 parts by mass

[0316] · Methyl ethyl ketone (MEK): 1200 parts by mass · Methyl isobutyl ketone (MIBK): 800 parts by mass

[0317] (Fabrication of positive electrode laminate and positive electrode)

[0318] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 1, except that the above composition 9 was used instead of the above composition 1.

[0319] (Fabrication of negative electrode laminates and negative electrodes)

[0320] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 1, except that the above composition 9 was used instead of the above composition 1.

[0321] (Production of lithium-ion secondary batteries)

[0322] A lithium-ion secondary battery was manufactured in the same manner as in Example 1, except that the positive and negative electrodes obtained in Example 9 were used.

[0323] <Example 10>

[0324] (Composition for forming a primer layer 10)

[0325] Composition 10 for forming a primer layer containing an epoxy resin was prepared by mixing each of the following components in a ball mill for 5 hours.

[0326] · Carbon powder (specific surface area; 150 m² / g): 30 parts by mass

[0327] · Epoxy resin (Epiklon H-205-60KM, manufactured by Dainippon Ink Co., Ltd.: 40 parts by mass

[0328] · Polyisocyanate (Coronate L, manufactured by Tosos): 5 parts by mass

[0329] · Silane-based coupling agent (KBM573, manufactured by Shin-Etsu Chemical Co., Ltd.): 25 parts by mass

[0330] · Methyl ethyl ketone (MEK): 1200 parts by mass · Methyl isobutyl ketone (MIBK): 800 parts by mass

[0331] (Fabrication of positive electrode laminate and positive electrode)

[0332] A positive electrode laminate and a positive electrode were fabricated in the same manner as in Example 3, except that the above composition 10 was used instead of the above composition 3.

[0333] (Fabrication of negative electrode laminates and negative electrodes)

[0334] A negative electrode laminate and a negative electrode were fabricated in the same manner as in Example 3, except that the above composition 10 was used instead of the above composition 3.

[0335] (Production of lithium-ion secondary batteries)

[0336] A lithium-ion secondary battery was manufactured in the same manner as in Example 3, except that the positive and negative electrodes obtained in Example 10 were used.

[0337] <Evaluation of Adhesion of Electrode Laminates for Capacitive Devices>

[0338] Each of the positive electrode laminate and the negative electrode laminate of the above examples was cut into a short sheet with a width of 2 cm × a length of 10 cm and fixed with the coating surface of the electrode composite facing upward. Cellophane tape was attached to the coating surface of the electrode composite, and the strength (N / cm) was measured 5 times when the tape was peeled in the 90° direction at a speed of 10 mm / min, and the average value was taken as the peel strength. The higher this value, the better the adhesion (bonding) by the primer layer. That is, the adhesion between the electrode composite and the current collector, which are bonded by the primer layer, is excellent.

[0339] The results are shown in Table 1 and Table 2.

[0340] <Evaluation of Charge / Discharge Cycle Characteristics of Lithium-ion Secondary Batteries>

[0341] For the lithium-ion secondary batteries prepared in each example, a cycle was performed in which the battery was charged to 4.3 V (voltage represents the voltage relative to lithium) at 25°C with a constant current equivalent to 0.2 C, and further charged until the current value at the upper charging limit voltage became 0.02 C, and then discharged to 3 V with a constant current equivalent to 0.2 C. The capacity retention rate (unit: %) of the discharge capacity at the 100th cycle relative to the discharge capacity at the first cycle was calculated and used as an indicator of the charge-discharge characteristics of the battery. A higher value of the capacity retention rate indicates superior performance.

[0342] In addition, 1 C represents the current value that discharges the standard capacity of the battery in one hour, and 0.5 C represents half that current value.

[0343] The results are shown in Table 1 and Table 2.

[0344] <Evaluation of Discharge Rate Characteristics of Lithium-ion Secondary Batteries>

[0345] A lithium-ion secondary battery prepared in each example was used, and at 25°C, it was charged to 4.3 V (voltage represents the voltage relative to lithium) with a constant current equivalent to 0.2 C, and further charged until the current value at the upper charging limit voltage became 0.02 C. Subsequently, the discharge rate characteristics were evaluated by discharging to 3 V with a constant current equivalent to 0.2 C, charging in the same manner as above, and discharging to 3 V with a constant current equivalent to 3 C. The retention rate of the discharge capacity after 3 C discharge (3 C discharge capacity), when the discharge capacity after 0.2 C discharge (0.2 C discharge capacity) is set to 100%, was calculated based on the following formula and used as the initial discharge capacity ratio. A high initial discharge capacity ratio indicates that the resistance within the electrode is low and excellent.

[0346] Discharge Capacity Ratio (%) = (3 C Discharge Capacity / 0.2 C Discharge Capacity) × 100

[0347] The results are shown in Table 1 and Table 2.

[0348]

[0349]

[0350] As shown in Tables 1 and 2, the positive electrode laminates and negative electrode laminates of Examples 1 to 8, which included copolymer A in the primer, all exhibited good adhesion. In addition, the lithium-ion secondary batteries obtained in Examples 1 to 8 had good charge-discharge cycle characteristics and discharge rate characteristics.

[0351] In contrast, the positive electrode laminate and negative electrode laminate of Example 9, in which a polymer other than copolymer A was used as a primer, had inferior adhesion. Also, the lithium-ion secondary battery obtained in Example 9 had inferior charge-discharge cycle characteristics and discharge rate characteristics. Also, although the positive electrode laminate and negative electrode laminate of Example 10 had adhesion, the lithium-ion secondary battery obtained in Example 10 had inferior charge-discharge cycle characteristics and discharge rate characteristics.

[0352] In addition, the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2021-050217 filed on March 24, 2021 are incorporated herein by reference and accepted as disclosure of the specification of the present invention.

Claims

Claim 1 A primer for a capacitor device electrode for forming a primer layer formed between a current collector and an electrode active material layer, comprising a fluorine-containing copolymer having a unit based on tetrafluoroethylene or chlorotrifluoroethylene, and a unit based on ethylene, hexafluoropropylene or perfluoro(alkyl vinyl ether), substantially not having a unit based on vinylidene fluoride, and also having an adhesive functional group capable of reacting with a hydroxyl group or forming a hydrogen bond. Claim 2 A primer according to claim 1, wherein the melting point of the fluorine-containing copolymer is 150°C or higher. Claim 3 A primer according to claim 1, wherein the fluorine-containing copolymer has one or more types selected from the group consisting of carbonyl-containing groups and hydroxyl groups as the adhesive functional groups. Claim 4 A primer according to claim 3, wherein the fluorine-containing copolymer has, as the adhesive functional group, at least one carbonyl-containing group selected from the group consisting of a carbonyl group having a carbonyl group between carbon atoms of a hydrocarbon group, a carbonate group, a carboxyl group, a haloformyl group, an alkoxycarbonyl group, and an acid anhydride group. Claim 5 A primer according to claim 1, wherein the fluorine-containing copolymer comprises a tetrafluoroethylene-based unit. Claim 6 A primer according to claim 1, wherein the fluorine-containing copolymer comprises ethylene-based units. Claim 7 A primer according to claim 1, wherein the fluorine-containing copolymer comprises a tetrafluoroethylene-based unit and an ethylene-based unit. Claim 8 In claim 1, a primer additionally containing a conductive material. Claim 9 A composition for forming a primer layer, comprising a primer for an electrode of a capacitor device as described in any one of claims 1 to 8 and a liquid medium. Claim 10 A composition according to claim 9, wherein the liquid medium is one or more selected from the group consisting of aqueous media, aliphatic compounds, aromatic hydrocarbons, alcohols, ethers, esters, ketones, nitrogen-containing compounds, sulfur-containing compounds, and fluorine-containing compounds. Claim 11 A composition according to claim 9, wherein the liquid medium is one or more selected from the group consisting of an aqueous medium, N-methylpyrrolidone, N,N-dimethylacetamide, and an aliphatic hydrocarbon compound having 6 to 10 carbon atoms and one carbonyl group. Claim 12 An electrode for a capacitor having a current collector and an electrode active material layer formed on the current collector, wherein the electrode for a capacitor has a primer layer comprising a primer for a capacitor electrode described in any one of claims 1 to 8 between the current collector and the electrode active material layer. Claim 13 An electrode for a capacitor having a current collector and an electrode active material layer formed on the current collector, wherein the electrode for a capacitor has a primer layer formed of a primer layer forming composition described in claim 9 between the current collector and the electrode active material layer. Claim 14 An electrode for a capacitor having a current collector and an electrode active material layer formed on the current collector, wherein the electrode for a capacitor has a primer layer formed of a powder of a primer for a capacitor electrode described in any one of claims 1 to 8 between the current collector and the electrode active material layer. Claim 15 A secondary battery having an electrode and an electrolyte for a storage device as described in claim 12.

Citation Information

Patent Citations

  • Binder composition for power storage device, electrode mixture for power storage device, electrode for power storage device, and secondary battery

    JP2018005972A